An??lise do impacto estrutural de polimorfismos de base ??nica n??o-sin??nimos (nsSNPs) presentes no gene da uroguanilina mediante simula????es por din??mica molecular de longa dura????o - Marcolino, Antonio Carlos Silveira (2016)
The guanylate cyclase activator 2B, also known as uroguanylin, is part of the guanylin peptide family, which includes peptides such as guanylin and lymphoguanylin. The guanylin peptides are related to sodium absorption inhibition and water secretion induction. Uroguanylin may be related to various pathologies such as chronic renal failure, congestive heart failure and nephrotic syndrome. Uroguanylin mutations have already been associated with essential hypertension. However, there are no studies on the structural changes in the uroguanylin???s protein that used single nucleotide polymorphisms through the use of molecular dynamics simulations. This study used 16 in silico SNP impact prediction tools to evaluate non synonymous SNPs and to select mutations considered as convergent deleterious, which were further analyzed through long time molecular dynamics simulations of 1 microsecond of duration. The results of the molecular dynamics simulations suggest that all SNPs considered as convergent deleterious suffered some kind of structural change, however, four of these nsSNPs have also undergone flexibility changes, possibly resulting in functional changes.